PENGARUH PENGUNGKAPAN AKUNTANSI LINGKUNGAN TERHADAP STOCK RETURN (Studi Empiris di BEI Periode 2016-2018) - Rifana Wahyu R.S.; Nur Diana; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTManufacturing companies are companies that process goods ranging from raw materials or raw materials to finished goods which are then sold to consumers. A manufacturing company is one company that can affect the surrounding environment. The process of processing raw materials into finished goods will produce waste, both in the form of solid, liquid, or gas. Waste from the industry can cause pollution of the environment around the company.. Disclosure of environmental accounting is a form of corporate responsibility and concern for the environment. The researcher conducted this study aimed to find out and analyze the effect of environmental accounting disclosures on annual financial statements on Stock Return. this study included quantitative research 16 manufacturing companies that met the criteria and used secondary data. Data analysis used descriptive statistical tests, normality tests, simple linear regression tests and hypothesis testing. Data analysis used descriptive statistical tests, normality tests, simple linear regression tests and hypothesis testing. analysis found that the disclosure of environmental accounting simultaneously did not significantly influence the stock return Stakeholder theory states that disclosure of social and environmental responsibilities carried out by the company is intended to fulfill the desires and information needs needed by stakeholders. Indirectly the existence of stakeholders can help the sustainability of a company's business. therefore the company must show the best performance so that stakeholders provide trust for the company. Thus stakeholders, especially investors, will be willing to invest in the company because of the trust and desire to get a profitable return.  Keywords: Environmental accounting and stock returns